PENGISLAMISAN SEJARAH ISLAM DI NUSANTARA DALAM CERAMAH USTAZ SALIM A FILLAH - Ahmad Anfasul Marom; Muh. Ulil Absor; M. Yaser Arafat; Raisatul Mufahamah (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The article focuses on the lectures of Salim A Fillah (SAF), a popular preacher known for his Islamist activism within the Prosperous Justice Party (PKS) in Indonesia. The data is obtained through digital observation and literature review. The analysis employs the Roland Barthes semiology method to examine SAF's lectures on the history of Islamization in Nusantara, which are widely available on platforms like YouTube. The denotation stage of the analysis involves SAF dividing the history of Islam's arrival in the archipelago into seven waves, each characterized by distinct discourse. However, during the connotation stage, it is revealed that SAF's periodization of Islamic history is framed by a narrative of Islamism. This means that SAF portrays the history of Islam in the archipelago as the history of Islamism. The article suggests that SAF implicitly preaches that the saints who spread Islam in the archipelago were individuals with missionary missions similar to present-day Islamists in Indonesia. Additionally, the article highlights SAF's emphasis on transnational Islamic movements like HTI and the Muslim Brotherhood, which are associated with the PKS, as continuations of the missionary efforts of these saints. Therefore, it concludes that SAF has constructed an Islamist narration of Islamic history in Indonesia. SAF also blurred the lines between historical facts and ideological storytelling